Entre aménagement du paysage et ménagement de la nature à Marseille: la trame verte à l’épreuve du local. - Jean Noël Consalès; Marie Goiffon; Carole Barthélémy (Développement Durable et Territoires)
Applied to urban territories, the green way highlights biodiversity-related issues within environmental development projects. The present article is an attempt to evaluate the local applications of this nationwide policy, by assessing the project in Marseille opposite to the potential green way of the territory. It stresses the key role that the urban fringe plays in this process. On the basis of a landscape-focused approach and an analysis of speech, it highlights the “green schizophrenia” expressed, in that area, towards some areas with natural character (planted wildlands). At the same time, these areas are in fact valorised reservoirs of biodiversity and land reserves.